2017
DOI: 10.1155/2017/8915104
|View full text |Cite
|
Sign up to set email alerts
|

A 10-Year Follow-Up of Two-Incision and Modified Watson-Jones Total Hip Arthroplasty in Patients with Osteonecrosis of the Femoral Head

Abstract: Long-term data and information indicating whether minimally invasive surgery (MIS) approaches are safe and effective with total hip arthroplasty (THA) are lacking. Between 2004 and 2006, 75 patients with alcohol-related osteonecrosis of the femoral head (ONFH) who underwent 75 THAs with the two-incision approach were studied. The medical records, radiographic parameters, and functional outcomes were collected prospectively. All data were compared with those for matched patients who underwent a modified Watson-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Generally, hip approaches can be broadly divided into three main categories depending on the anatomical relationship to the greater trochanter; anterior, lateral, and posterior approaches (7,9,10). Additionally, intermediate approaches in-between any two of the above have been established (10)(11)(12)(13). Overall, posterior approaches provide wider exposure and spare the abductors muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, hip approaches can be broadly divided into three main categories depending on the anatomical relationship to the greater trochanter; anterior, lateral, and posterior approaches (7,9,10). Additionally, intermediate approaches in-between any two of the above have been established (10)(11)(12)(13). Overall, posterior approaches provide wider exposure and spare the abductors muscles.…”
Section: Introductionmentioning
confidence: 99%
“…We have also found that age ≥ 55 years and preoperative degenerative Tönnis stage II were independent risk factors for future THA conversion. With our considerable experience in THA via the modified Watson-Jones approach [26, 27], we were able to perform the osteochondroplasty on the head-neck junction with a small intermuscular interval, and use arthroscopic technique to manage the labral and cartilage injuries in patients with cam-type FAI.…”
Section: Discussionmentioning
confidence: 99%